ANALISIS NERACA AIR SECARA METEOROLOGIS DI DAS KEDUANG, JAWA TENGAH - Kumalajati, Erlynda; Sabarnudin, Sambas; Budiadi; Sudira, Putu (Jurnal Wana Tropika, 2015)
Study on meteorological water balance in Keduang watershed, Central Java, aimed to find a balance between the need and meteorological availability of water in the Keduang watershed. Water demand is calculated by using the standard water requirements for this type of irrigation and non-irrigation needs. Types of non-irrigation water requirements include the need for water for domestic, office buildings, health facilities, lodging / hotels, educational facilities, religious facilities, industries, and markets, as well as livestock. Standards need water used is ISO 19-6728.1-2002 and Planning Criteria DGHS Department of Public Works in 1996. The availability of water is calculated using the water balance approach meteorological Turc-Langbein. The data used is the data in 2013 and analyzed using quantitative description.The results showed that 1) the need for water in the Keduang watershed 81,063,567.42 m3 / year, while 2) the availability of water in the meteorological amounted 280,160,992.62 m3 / year so that the difference amounted to 199,097,425.19 water m3 / year. From the results of these calculations, we can conclude that the water availability in the Keduang watershed is sufficient for fullfilling the water requirements. Keywords : Water requirements, water availability, water balance, Keduang watershed